ANALYSIS OF THE FILM “THE MAN WHO KNEW INFINITY : SPEECH ACT STUDY - Syahrul Effendi Lubis (CENDEKIA INDONESIA, 2023)
The research method employed was descriptive qualitative research, and the goal of the study was to examine the forms and meanings of speech acts in the film The Man Who Knew Infinity's dialogues. The results show that there are 45 forms and meanings of speech acts in fifteen dialogues containing Locutionary, Illocutionary, and Perlocutionary Acts in the dialogues of Matthew Brown's film